Comparison of the effects of direct and indirect education of sexually transmitted infections on knowledge and attitude of male nursing and medical students of Shahid Beheshti University of Medical Sciences, Tehran – Iran, 2018 - Farazmand, Khatereh; Azin, Payam; Eskandari, Saber; Farazmand, Pegah; Keshavarz Mohammadi, Nastaran (Archives of Men’s Health, 2020)
Introduction: It is very important to prevent Sexually Transmitted Diseases (STIs) as they cause many other health problems with serious complications. In fact, prevention is the most effective mean of dealing with STIs. In saying that, the basic requirements of prevention include appropriate health education on the subject. This study compares the effectiveness of two health education programs regarding bacterial STIs among male students at Nursing and Medical Schools of Shahid Beheshti University of Medical Sciences and Health Services in Tehran. Materials and Methods: The quasi-experimental study included 430 male students aged between 18 and 30 who were majoring in nursing and medical field. Two faculties were selected through purposeful non-random sampling. A valid and reliable researcher-made questionnaire was filled out in two steps (before and one month after the training). The training interventions in direct education group included a lecture along with a session of questions and answers (Q&As) for one and a half hours. On the other hand, the indirect education only included a weblog on the topic of STIs. The statistical tests were employed to analyze the collected data in SPSS 22. Results: Generally, students’ knowledge and attitudes toward this subject were at a moderate level before the intervention, and only %18.4 of them were well-aware of bacterial STIs. In fact, %44 of the respondents had positive attitudes toward those diseases. The research results indicated that the educational intervention managed to increase the awareness and attitudes of the students in relation to STIs in the two case groups in comparison with the control group. However, the different methods of education produced similar results and had no significant differences. Moreover, attitudes increased in the weblog group slightly more than the lecture group. Conclusion: According to the findings of this research, The weblog intervention had more effects on their attitudes than the lecture intervention. Therefore, the modern training method based on the use of the internet (weblog) can be used effectively as an alternative or supplement to traditional training methods.